Minutes of consultation workshop on the project consortium for Scaling-up Climate Smart Agriculture in South Asia (C-SUCSeS): Brainstorming the challenges and opportunities of tackling climate change in the region - International Food Policy Research Institute; South Asian Association for Regional Cooperation (SAARC) Agriculture Center (International Food Policy Research Institute, 2022)
Consortium for Scaling-up Climate Smart Agriculture in South Asia (C-SUCSeS) is a four-year joint initiative between South Asian Association for Regional Cooperation (SAARC) Agriculture Center (SAC), International Food Policy Research Institute (IFPRI), International Fund for Agricultural Development (IFAD), and the SAARC Development Fund (SDF). The program aims to foster partnership and cooperation between SAARC, National Agricultural Research and Extension Systems (NARES), IFPRI, and SAARC governments on the Climate-Smart Agriculture (CSA) agenda. The project also intends to support agricultural researchers’ to generate and facilitate delivery of technological solutions to smallholder and women farmers, with a specific priority on the intensification and resilience of smallholder agriculture, contributing, inter alia, to increasing water management efficiency, promote innovative, pro-poor approaches and technologies with demonstrated scaling-up potential, strengthen partners’ institutional and policy capacities, enhance policy engagement, and generate and share knowledge.